Old Testament/Ancient Near Eastern Permucite Index. An Exhaustive Indexing System for Old Testament and Ancient Near Eastern Studies (1978)
Infodex; Per annum $250.00; Master Index (p. 33-140) of the 476 titles is completed by a Citation Index (p. 143-217), a “Permutitle” Index of double lemmata (p. 221-241), and Author Index (p. 245-251)